Use of organominerals in agriculture - Lopes, Tatiany Arrais; Backes, Clarice; Santos, Alessandro José Marques; Sousa, João Eduardo Reis; Baião, Danilo Corrêa; Ribon, Adriana Aparecida (Seven Editora, 2024)
Animal production systems generate a high amount of organic waste, which if disposed of irrationally can cause contamination of both soil and water. Aviary litter is one of these examples, which, due to the high amount of organic matter and nutrients, has the potential to be applied as an organic fertilizer, totally or partially replacing chemical fertilizers, which are essential for plant development. The use of organic fertilizers can also reduce fertilization costs, which are high, mainly due to dependence on imports. Treatments such as composting are important to reduce the pathogenic load of the material, ensuring greater safety in its use. Many positive responses have already been scientifically proven, bringing benefits such as soil improvement and increased yields, both of annual crops and perennial pastures. The recommendation of the dose of the organic fertilizer can be carried out in order to meet the demand for P, which is found in low concentrations in Brazilian soils.  To increase the concentration of nutrients in organic fertilizers and make them more balanced, they can be complemented with chemical fertilizers, generating organominerals. The proper use of residues, especially poultry litter, combined with chemical fertilizers can contribute satisfactorily to farmers, due to the possibility of reducing the operational cost of production and chemical fertilizers. DOI:https://doi.org/10.56238/sevened2023.001-018